Test The Growth Process of Hair Follicles by Administering Coconut and Candlenut Oil to The Entire Back of White Rats (Rattus Norvegicus) Of the Wistar Strain - Mulan Mulan; Hendrianto Hendrianto; Sahna Ferdinand (International Journal of Health and Pharmaceutical (IJHP), 2024)
Hair serves a variety of purposes, including thermoregulation and protection. Hair regulates temperature in nonhuman animals, including primates, by holding heat or preventing cold. Hair can also be used for disguise and as a sexual attractant. Human hair is thinner and lighter than that of primates. The purpose of this study was to determine and test the efficacy of providing a coconut oil and candlenut oil mixture in the process of hair development in Wistar rats (Rattus norvegicus). The study's findings indicate that a combination containing 80% coconut oil and 20% candlenut oil is the most efficient in stimulating hair development in white rats (Rattus norvegicus) of the Wistar strain. This hair growth acceleration is possible because coconut oil contains a high concentration, precisely 80%. Because coconut has a high amount of lauric acid, it has numerous health benefits, including good hair.